Identification Of Potential Hazards In Palm Oil Companies In The Sterilizer Section Using The HIRARC Method - Wahyudin, Wahyudin; Sofiyanurriyanti, Sofiyanurriyanti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Worker safety is a critical factor in the continuity of an oil palm industry because the progress of the palm oil industry is also influenced by the availability of safety guarantees for its workers. Based on the results of the study, it was shown that the highest percentage of accident risk assessment was at the sterilizer work station (boiling FFB) using the HIRARC method, namely in the activity of pulling the cable sling from the winch and then attaching the hook to the lorry from the transfer carriage with 25 the risk of accidents occurring with a percentage of 33.33 % and categorized into extreme, for the second highest accident risk assessment, namely in the activity of pulling a lorry using a winch and in the activity of opening the sterilizer door and lowering the sterilizer bridge with a work accident risk of 16 times with a percentage rate of 21.33% and categorized into high incident and the risk of work accidents, namely in the activity of releasing the hook and carrying it then installing it to the last lorry and in the activity of pulling and carrying sling cables from the winch with a risk of accidents of 9 times the incidence of work accidents with a percentage rate of 12.00% and categorized into incident medium. Keywords: Minimizing the Risk of Occupational Accidents and the HIRARC Method